No detectable association of the ESR Pvull mutation with sow productivity in a Meishan x Large White F2 population - Gibson, John P.; Jiang, Z.H.; Robinson, J.A.B.; Archibald, A.L.; Haley, C.S. (Wiley, 2002)
The polymorphism at the PvuII recognition site in the ESR gene showed no statistically significant association with sow productivity traits in a Meishan x Large White F2 population. Estimates of the effect on litter size were. however, in the opposite direction and statistically different from previously published estimates. Taken together with results from other publications, results here indicate that this PvuII polymorphism displays different degrees of linkage disequilibrium with a gene or genes controlling litter size in different populations.